Is a Sorrow Shared a Sorrow Doubled? Parental Unemployment and the Life Satisfaction of Adolescent Children - Melanie Borah; Andreas Knabe; Christine Lücke (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines possible spillover effects of parental unemployment on the subjective wellbeing of 12- to 21-year-old children. Using German panel data (SOEP), we show that unemployment of fathers and mothers is negatively associated with their children's life satisfaction. When controlling for time-invariant individual heterogeneity, our results suggest that maternal unemployment has negative effects, while no effect of fathers' unemployment can be detected. In subgroup analyses, we do not find differential impacts between sons and daughters or between younger and older children. Further results suggest that the impact of parental unemployment differs between high- and low-unemployment regions.
Keywords: I31; J13; J63; J64; 330; unemployment; life satisfaction; happiness; children; intergenerational transmission